Why do mutual funds hold lottery stocks? - Vikas Agarwal; Lei Jiang; Quan Wen (University of Cologne, Centre for Financial Research (CFR), 2020)
We provide evidence regarding mutual funds' motivation to hold lottery stocks. Funds with higher managerial ownership invest less in lottery stocks, suggesting that managers themselves do not prefer such stocks. The evidence instead supports that managers cater to fund investors' preference for such stocks. In particular, funds with more lottery holdings attract larger flows after portfolio disclosure compared to their peers, and poorly performing funds tend to engage in risk shifting by increasing their lottery holdings towards year-ends. Funds' aggregate holdings of lottery stocks contribute to their overpricing.
Keywords: G11; G23; 330; lottery stocks; risk shifting; fund performance; investor flows; stock mispricing